Community Diagnosis Activity Report in Efforts to Increase Tuberculosis Preventive Therapy Acceptance Rate in Dukuh Village, Cikupa Health Center Work Area, Cikupa Subdistrict, Tangerang Regency, Banten Province Period: May 2, 2025 - June 28, 2025 - Cindy Clarissa S; Zita Atzmardina; Irvan Baharits (Malahayati Nursing Journal, 2025)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis complex. Tuberculosis Preventive Therapy (TPT) is necessary for individuals at high risk of contracting TB to prevent transmission. However, the uptake rate of TPT remains low in areas with the highest number of TB cases. From January to April 2025, the number of TPT recipients in the Cikupa Community Health Center's working area was only 41 people, falling short of the target of 91. The objective was for all participants to demonstrate increased knowledge following the intervention and to be able to correctly perform the intervention. Data was collected through a mini-survey conducted among the community within the Cikupa Community Health Center's working area. The collected data was then analyzed using the Blum Paradigm to identify problems. Problem prioritization was determined using the non-scoring Delphi method. A Fishbone diagram was used to identify the root causes of the problem. During the intervention, pre-tests and post-tests were administered to assess the knowledge of Dukuh village residents before and after the intervention. The PDCA (Plan-Do-Check-Act) cycle and a systems approach were used for monitoring and evaluation. The problem identification using the Blum Paradigm indicated that 'Lifestyle' was the primary contributing factor. In Intervention 1, a total of 26 participants showed an increase in correct answers on their post-test compared to their pre-test, and 31 participants achieved a post-test score of ≥ 70. For Intervention 2, three participants were able to correctly re-demonstrate the procedure. Following Interventions 1 and 2, the program was declared successful. It is expected that these interventions will lead to an increase in the number of TPT recipients in the Dukuh Village area. Keywords: Tuberculosis, TPT, Community Diagnosis